Effect of bleaching condition on thermal properties and UV transmittance of PVA/cellulose biocomposites - Ng, T.S.; Ching, Yern Chee; Awanis, N.; Ishenny, N.; Rahman, M.R. (Taylor & Francis, 2014)
The aim of this study was to investigate the effect of treated cellulose with different bleaching conditions on the poly(vinyl alcohol) matrix. Cellulose was extracted from oil palm empty fruit bunch fibre through chlorite bleaching, alkali treatment and acid hydrolysis. A casting technique was employed to prepare poly(vinyl alcohol)/fibre composites. Poly(vinyl alcohol) composites with various loadings of cellulose were prepared by using the treated cellulose with 8 hours bleaching. Composite films were characterised by thermogravimetric analysis and UV/Vis spectrometry. Higher loading of the treated cellulose into PVA composite resulted in a lower decomposition temperature, and a relatively better transmission in the range of visible light. Poly(vinyl alcohol) reinforced cellulose with a longer bleaching period allowed higher transmittance of light because of more lignin removed. Poly(vinyl alcohol) composites reinforced with treated cellulose gave better thermal stability without differing much its clarity compared to the pure PVA.